“La nulidad de sentencia como consecuencia de la falta de citación en legal y debida forma a la parte demandada; y, su incidencia en el debido proceso en los juicios ordinarios de prescripción extraordinaria adquisitiva de dominio tramitados en la unidad judicial civil con sede en el cantón Riobamba, provincia de Chimborazo, periodo 2016” - Gladys Mercedes, Morocho Plasencia (2017)
The present research work has as its theme: The nullity of sentence as a consequence of the lack of citation in legal and due form to the defendant; and its effect on due process in ordinary judgments of extraordinary acquisition prescription of jurisdiction processed in the Civil Judicial Unit based in the Riobamba canton, Chimborazo province, period 2016. Six chapters, whose content includes units, themes and sub-themes related to the subject matter of research work, structure it.In Chapter I, in this chapter, the Reference Framework is defined. - In which it consists: the approach of the problem and formulation of the problem, determine the objectives of the research; general and specific, in addition the justification and importance of the work; reasons for its elaboration. In Chapter II, the Theoretical Framework is developed. - Through a doctrinal, legal and critical study of the investigation, for which it is the broadest chapter, for this reason has been divided into five units, in the following order: Unit I.- deals with the citations, where it begins with doctrinal definitions, forms of citation, effects, importance and last consequences that produces when not citing in the correct way, in the COGEP. Unit II.- We will talk about nullity, doctrinal definitions, substantial solemnities, nullity for lack of citation, effects of nullity and concludes with regard to the main issue nullity of sentence, all based on COGEP. Unit III.- deals with the prescription in general, definitions, the prescription in the Ecuadorian Civil Code, the prescription within our Constitution of the Republic, concluding with the classes of the prescription. Unit IV.- It deals with the acquisition prescription of domain, etymology, definition, historical antecedents, rules to acquire the extraordinary prescription of dominion, requirements and the ordinary procedure with the COGEP. Unit V. - everything about due process, begins with a brief historical overview, doctrinal definitions, applicability within our Ecuadorian legislation, effects caused to the procedural parties against whom the nullity has been declared and concludes this unit with case study analysis. Chapter III describes the methodological framework. - where the field investigation is carried out, the same one that has been carried out after previous investigation to the Lawyers and free exercise of Riobamba; and, Judges and Judges of the Civil Judicial Unit based in the Riobamba canton, through surveys and interviews, the interpretation and discussion of the results were also performed to corroborate the hypothesis. Chapter IV establishes the administrative framework; where the resources and costs used for the development of research are exposed. In Chapter V, where the conclusions and recommendations are verified, with strict relation to the objectives, and the results achieved in the field research, finally in chapter VI, the bibliography and annexes are established.